Influence of copper on expression of nirS, norB and nosZ and the transcription and activity of NIR, NOR and N2OR in the denitrifying soil bacteria Pseudomonas stutzeri. Issue 3 (2nd March 2016) - Black, Amanda; Hsu, Pei‐Chun L.; Hamonts, Kelly E.; Clough, Tim J.; Condron, Leo M.
Summary: Reduction of the potent greenhouse gas nitrous oxide (N2 O) occurs in soil environments by the action of denitrifying bacteria possessing nitrous oxide reductase (N2 OR), a dimeric copper (Cu)‐dependent enzyme producing environmentally benign dinitrogen (N2 ). We examined the effects of increasing Cu concentrations on the transcription and activity of nitrite reductase (NIR), nitric oxide reductase (NOR) and N2 OR in Pseudomonas stutzeri grown anaerobically in solution over a 10‐day period. Gas samples were taken on a daily basis and after 6 days, bacterial RNA was recovered to determine the expression of nirS, norB and nosZ encoding NIR, NOR and N2 OR respectively. Results revealed that 0.05 mM Cu caused maximum conversion of N2 O to N2 via bacterial reduction of N2 O. As soluble Cu generally makes up less than 0.001% of total soil Cu, extrapolation of 0.05 mg l −l soluble Cu would require soils to have a total concentration of Cu in the range of, 150–200 μg g −1 to maximize the proportion of N2 O reduced to N2 . Given that many intensively farmed agricultural soils are deficient in Cu in terms of plant nutrition, providing a sufficient concentration of biologically accessible Cu could provide a potentially useful microbial‐based strategy of reducing agricultural N2 O emissions. Abstract : Reduction of the potent greenhouse gas nitrous oxide (N2O) occurs in soil environments by the action of denitrifying bacteria possessing nitrous oxide reductase (N2OR), a dimeric copper (Cu)‐dependent enzyme producing environmentally benign dinitrogen (N2). We examined the effects of increasing Cu concentrations on the transcription and activity of nitrite reductase (NIR), nitric oxide reductase (NOR) and N2OR in Pseudomonas stutzeri grown anaerobically. Results revealed that 0.05 mM Cu caused maximum conversion of N2O to N2 via bacterial reduction of N2O.